1999
DOI: 10.1017/s0950268899002538
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for monoinfections and coinfections with HIV, hepatitis B and hepatitis C viruses in northern Spanish prisoners

Abstract: A cross-sectional study was conducted in prisons of Cantabria (northern Spain) from June 1992 to December 1994. Inmates were asked to participate in a survey on prevalence and risk factors for monoinfections and coinfections with HIV, HBV and HCV. Crude and multiple odds ratios of risk factors were calculated (by polychotomous logistic regression). Prevalence of coinfections was higher than that of monoinfections. IDU risk factors were the main independent variables associated with monoinfections and coinfecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 51 publications
4
13
1
Order By: Relevance
“…A similar association has been reported in a study conducted among IDUs in Spain. 36 Several authors have discussed tattooing as a mode of HCV and HIV transmission. [37][38][39] Other studies have noted a high prevalence of tattoos among anti-HCV positive patients with chronic hepatic disease 40 and among persons attending HIV In this study we found that sex with a casual or commercial sex partner without using condoms was not associated with HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…A similar association has been reported in a study conducted among IDUs in Spain. 36 Several authors have discussed tattooing as a mode of HCV and HIV transmission. [37][38][39] Other studies have noted a high prevalence of tattoos among anti-HCV positive patients with chronic hepatic disease 40 and among persons attending HIV In this study we found that sex with a casual or commercial sex partner without using condoms was not associated with HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Since tattooing in jail or prison is generally performed using non-sterile equipment such as paper clips and guitar strings, it is not surprising that this practice would be a risk factor for acquisition of bloodborne pathogens, as has been seen in Spain [23]. In other countries, HCV infection has been associated with folk medicine practices, tattooing, body piercing and commercial barbering [24][25][26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, while the World Health Organization (WHO) estimates that about 3% of the world's population has been infected with the hepatitis C virus (HCV), [37] estimates of the prevalence of HCV in prisons range from 4.8% in an Indian jail [38] to 92% in two prisons in northern Spain [39,40]. …”
Section: Reviewmentioning
confidence: 99%